Application of the Status of Justice Collaborator in the Criminal Justice System in Indonesia (Case Study: Decision of Central Jakarta District Court Number 41/Pid.sus/TPK/ 2017/PN. JKT) - Setiawan, Waras; Hasibuan, Edi Saputra; Atmoko, Dwi (Green Publisher Indonesia, 2024)
In Indonesian criminal law, the status of a Perpetrator Witness (Justice Collaborator) has significant legal consequences. With the entry of this Justice Collaborator regulation, the threat of criminal punishment will be less effective against perpetrators of serious crimes. This will make it more difficult to identify the main perpetrators in cases of crimes committed together, and will be a new strategy to avoid the threat of high punishment because the status of a Justice Collaborator is guaranteed to get leniency for serious crimes committed. The enactment of the regulation on the status of Justice Collaborator in corruption criminal justice which provides a guarantee of a reduction in punishment for perpetrator witnesses is seen as very counterproductive with a very high criminal threat for corruption perpetrators as perpetrators of certain crimes (serious crimes). Most people in Indonesia even strongly agree that the criminal threat for the perpetrators of corruption crimes is the death penalty, so great are the hopes of people who want no more corruption crimes that are very detrimental to the state and the people of Indonesia.